Clinical observation on the effect of Chinese medicine-"TCM formula" intervention on recurrence and metastasis of triple negative breast cancer. (August 2020) - Wang, Yi; Li, Jian-Wei; Qin, Yue-Nong; Sun, Chen-Ping; Chen, Jia-Jing; Ruan, Yi-Ying; Chen, Li-Xin; Liu, Sheng; Liu, Guang-Yu
Highlights: This study used a prospective cohort study to observe the effect of triple-negative breast cancer on the 2-year disease-free survival rate with or without "TCM Formula". Through K-–M survival analysis, TNBC patients with age ≤35 years and regional lymph node stage N1 may be the benefit group of "TCM Formula"(P < 0.05). Logistic multivariate regression analysis predicted that "TCM Formula" could reduce the disease-related recurrence and metastasis rate by 11% (OR=0.89, 95 % CI 0.37−0.956, P < 0.05). Abstract: Objective: This study used a prospective cohort study to observe the effect of triple-negative breast cancer on the 2-year disease-free survival rate with or without "TCM formula". Methods: From November 1 st, 2016, the first patient was enrolled in the cohort study. A total of 356 patients were enrolled on January 30, 2019. Among them, 154 cases were followed up for 2 years. During the follow-up, there were 6 cases of shedding, so 6 cases were affected. A total of 148 cases were included in the analysis, including 73 in the exposed group and 75 in the non-exposed group. The exposed group was given "TCM formula" on the basis of standardized treatment, and the non-exposed group was treated with simple triple-negative breast cancer. The two groups visited each of the three months. The interview included safety examination (hematology and imaging). The endpoint was the difference in 2-year invasive disease-free survival between the exposed and non-exposed groups and the safety of the "TCM formula". Results: There were 6 cases of shedding during the experiment and the shedding rate was 3.9 %. The 2-year rate of invasive disease-free survival in the exposed team was 88.7 % and the non-exposed group was 82.5 %. Logistic multivariate regression analysis predicted that "TCM formula" could reduce the disease-related recurrence and metastasis rate by 11 % (OR = 0.89, 95 % CI 0.37−0.956, P ＜0.05). Through K–M survival analysis, TNBC patients with age ≤35 years and regional lymph node stage N1 may be the benefit group of "TCM formula"( P ＜0.05). During the study, the incidence of total adverse events was 8.2 % in the exposed group, mainly manifested as stomach discomfort, diarrhea, and hepatocyte damage. Conclusion: 1. In the exposed group, the two-year rate of invasive disease-free survival increased by 6.2 % compared with the non-exposed group( P ＞0.05). 2. According to K–M survival analysis, TNBC patients with age ≤35 years and regional lymph node metastasis to N1 may be potential beneficiaries of "TCM formula". 3. "TCM Formula" is safe and tolerable to most patients.